Biomarkers to predict advanced liver diseases - Alenezi, Yusef (2024)
Background: Chronic liver disease (CLD) is one of the leading causes of morbidity and mortality, accounting for more than two million deaths annually worldwide. In recent years, Non-alcoholic Fatty Liver Disease (NAFLD) has been a fast-emerging cause of CLD, which can progress to advanced conditions such as liver cirrhosis, hepatocellular carcinoma (HCC), and liver failure. While the condition of simple steatosis in NAFLD patients is usually benign, the risk of progression to advanced CLD underscores the importance of early detection, as late diagnosis frequently leads to poor patient outcomes. As a result, considerable effort is now being made to find non-invasive methods for the early detection of CLD.